College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 6 - Section 6.3 - Exponential Functions - 6.3 Assess Your Understanding: 4

Answer

The average rate of change is $3$ units.

Work Step by Step

RECALL: The average rate of change of a function from $x=a$ to $x=b$, where $a \gt b$, is given by the formula: $\text{average rate of change} = \dfrac{f(b) - f(a)}{b-a}$ Use the formula above to obtain: $\text{average rate of change}$ $\\= \dfrac{f(b) - f(a)}{b-a} \\=\dfrac{f(4)-f(0)}{4-0} \\=\dfrac{(3\cdot 4 - 5) - (3 \cdot 0 - 5)}{4} \\=\dfrac{7-(-5)}{4} \\=\dfrac{7+5}{4} \\=\dfrac{12}{4} \\=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.